2015
DOI: 10.1089/acm.2014.0009
|View full text |Cite
|
Sign up to set email alerts
|

Tian Jiu Therapy for the Treatment of Asthma in Adult Patients: A Meta-Analysis

Abstract: All studies indicated that tian jiu therapy has a positive effect on adults with asthma and that it is relatively safe because of its noninvasive nature. However, the limitations of the research design of the existing studies resulted in high risk of bias. More randomized controlled trials of better methodologic quality are needed to further confirm efficacy and safety of this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[43] Chan et al performed a meta-analysis and found that san fu tian (a form of SAAT) therapy has positive effects on adult asthma and this technology is relatively safe because of its noninvasive nature. [15] The results of Shi et al indicated SAAT with Shenhuang plaster reshaped the composition of the microbiota, especially butyrate-producing gut bacterium, and promotes intestinal peristalsis, and the combination of paclitaxel with Shenhuang SAAT exerted potent immunostimulatory effects. [23] At present, there have been several studies applying SAAT or other forms of acupuncture to the remission of coronavirus disease 2019-related symptoms, including headache, [46] diarrhea, [47] and fatigue.…”
Section: Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…[43] Chan et al performed a meta-analysis and found that san fu tian (a form of SAAT) therapy has positive effects on adult asthma and this technology is relatively safe because of its noninvasive nature. [15] The results of Shi et al indicated SAAT with Shenhuang plaster reshaped the composition of the microbiota, especially butyrate-producing gut bacterium, and promotes intestinal peristalsis, and the combination of paclitaxel with Shenhuang SAAT exerted potent immunostimulatory effects. [23] At present, there have been several studies applying SAAT or other forms of acupuncture to the remission of coronavirus disease 2019-related symptoms, including headache, [46] diarrhea, [47] and fatigue.…”
Section: Groupmentioning
confidence: 99%
“…[21,22] Correspondingly, the main acupuncture points used in combination include the Bladder meridian (BL), Ren meridian, and Du meridian according to clinical syndrome differentiation. [13,15] Specifically, BL13 (Feishu) is the most fundamental point for AAT, followed by BL17 (Geshu), BL20 (Pishu), and BL23 (Shenshu) acupoints. [19,23,24] In the Chinese medical system, a season-based AAT approach has also been applied to improve or prevent recurrent seasonal diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CWMT has the advantages of being low cost and simple (take drugs) compared to AAT with CWMT (10,11). However, as well as having poor overall efficacy, long-term administration of western medicines can cause adverse reactions and the development of drug resistance during treatment (11).…”
Section: Original Articlementioning
confidence: 99%